The Extended Erlang-Truncated Exponential distribution: Properties and application to rainfall data. Issue 6 (June 2017) - Okorie, I.E.; Akpanta, A.C.; Ohakwe, J.; Chikezie, D.C.
Abstract: The Erlang-Truncated ExponentialETE distribution is modified and the new lifetime distribution is called the Extended Erlang-Truncated ExponentialEETE distribution. Some statistical and reliability properties of the new distribution are given and the method of maximum likelihood estimate was proposed for estimating the model parameters. The usefulness and flexibility of theEETE distribution was illustrated with an uncensored data set and its fit was compared with that of theETE and three other three-parameter distributions. Results based on the minimized log-likelihood ( − ℓ ˆ ), Akaike information criterion (AIC), Bayesian information criterion (BIC) and the generalized Cramér–von Mises W ⋆ statistics shows that theEETE distribution provides a more reasonable fit than the one based on the other competing distributions.